Heart rate-based lactate minimum test: a reproducible method. Issue 6 (28th February 2008) - Strupler, M; Mueller, G; Perret, C
Abstract : Objective: To find the individual intensity for aerobic endurance training, the lactate minimum test (LMT) seems to be a promising method. LMTs described in the literature consist of speed or work rate-based protocols, but for training prescription in daily practice mostly heart rate is used. The aim of the present study was to investigate the reproducibility of a new heart rate-based LMT protocol. Design: 20 subjects each underwent four LMTs on a cycle ergometer. The LMT consisted of a first part (Conconi test) to induce lactate accumulation and a second part (incremental protocol) with stages of 5 min starting beyond the aerobic threshold. During these stages work rate was adjusted to reach predetermined heart rates, which were calculated for every single test from heart rate (HR) at rest and maximum HR. Lactate was measured after each stage to define the lactate minimum (LM) and the corresponding HR. Setting: Institute of Sports Medicine. Participants: 20 healthy and endurance-trained individuals (13 men, seven women). Main outcome measures: Reproducibility of heart rate at LM. Results: The reproducibility of heart rate at LM was high (coefficient of variation (CV) = 2.1%). The reproducibility of work rate at LM was good (CV = 6.7%). CV for lactate concentrations at LM was 17.4%. High interindividual differences at LM were found in heart rate (range 149–178 beats/min) and lactate levels (range 1.2–6.8 mmol/l). Conclusion: The LMT using a heart rate-based protocol is a reproducible method of assessing HR at an exercise intensity where an equilibrium exists between blood lactate accumulation and elimination.